2011
DOI: 10.1007/s11367-011-0279-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing agricultural soil acidification and nutrient management in life cycle assessment

Abstract: Purpose This paper describes part of the first detailed environmental life cycle assessment (LCA) of Australian red meat (beef and sheep meat) production. The study was intended to assist the methodological development of life cycle impact assessment by examining the feasibility of new indicators for natural resource management (NRM) issues relevant to soil management in agricultural LCA. This paper is intended to describe the NRM indicators directly related to agricultural soil chemistry. Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The effects of grazing and nutrient losses from pastures are reflected, as proposed by Peters et al (2011), in indicators of terrestrial acidification observed in ES and IS systems, albeit differently. Although there is a less soil erosion in the IS due to the control of the animal's permanence in the paddocks and forage supply, there is decrease in soil cover and increased the potential losses of nutrients in the ES from the continuous selective grazing.…”
Section: Terrestrial Acidification and Freshwater Eutrophicationmentioning
confidence: 94%
“…The effects of grazing and nutrient losses from pastures are reflected, as proposed by Peters et al (2011), in indicators of terrestrial acidification observed in ES and IS systems, albeit differently. Although there is a less soil erosion in the IS due to the control of the animal's permanence in the paddocks and forage supply, there is decrease in soil cover and increased the potential losses of nutrients in the ES from the continuous selective grazing.…”
Section: Terrestrial Acidification and Freshwater Eutrophicationmentioning
confidence: 94%
“…Supplementation with AA reduced N in the feed and excreta, leading to reduced ammonia emissions. Peters et al (2011) suggested that reducing the leaching of soil N coming from manure might be the best way to balance the N budget without causing acidification. The minor difference in AP between A2 and A3 was due to the reduction in monocalcium phosphate, which is produced from burnt chalk (CaO) and phosphoric acid contributing to AP.…”
Section: Acidification Potentialmentioning
confidence: 99%
“…Mechanisms for this acidification have been evaluated in many reports (e.g. Khan, ; Shi et al ., ; Peters et al ., ). Guo et al .…”
Section: Discussionmentioning
confidence: 97%